2017
DOI: 10.4314/tjpr.v16i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of plasmidmediated beta-lactamase genes among nosocomial <i>Staphylococcus aureus</i> isolated in Taiwan

Abstract: Purpose: To analyze the drug susceptibility phenotypes and the patterns of plasmid-mediated β-lactamase genes among nosocomial Staphylococcus aureus drug resistance isolates in Taiwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…All samples from poultry and layer farm have blaTEM gene. The similar result showed in Iran and Taiwan where 100% beta lactamase resistant strain have a blaTEM gene (Yang et al, 2017;Nouri-Gharajalar et al, 2019). BlaTEM gene encodes most encountered bacteria â-lactamase (Xu et al, 2014).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…All samples from poultry and layer farm have blaTEM gene. The similar result showed in Iran and Taiwan where 100% beta lactamase resistant strain have a blaTEM gene (Yang et al, 2017;Nouri-Gharajalar et al, 2019). BlaTEM gene encodes most encountered bacteria â-lactamase (Xu et al, 2014).…”
Section: Resultssupporting
confidence: 78%
“…BlaTEM gene encodes most encountered bacteria â-lactamase (Xu et al, 2014). Most strains, which have blaTEM gene, exhibited a high degree of resistance to â-lactam antibiotics in China and Taiwan (Yang et al, 2017). Modifcation of penicillin-binding protein (PLP2a) induces inactivity of penicillin and other beta lactam antibiotics; and it will develop cross-resistance of multiple antibiotics (Bounar-Kechih et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The blaTEM was detected in most isolates, which was positively correlated with the penicillin G resistance phenotype. Previously, studies reported a high frequency of the blaTEM gene in foodborne and clinical isolates (80% and 100%, respectively) (Xu et al 2014;Yang et al 2016). Resistance to methicillin in S. aureus is primarily mediated by the mecA gene, which encodes the low-affinity penicillin-binding protein 2a (PBP2a) (Rolo et al 2017).…”
Section: Antibiotic Resistance Marker Genementioning
confidence: 99%